Young female migrants and job placement brokers in Addis Ababa, Ethiopia - Erulkar, Annabel; Hailu, Eyasu (Frontiers in Reproductive Health, 2024)
Introduction Rates of urbanization in Ethiopia are high and adolescent girls and young women are predominant among those who move from rural to urban areas. Young women frequently undertake rural-urban migration on their own or with a friend, and with little planning for their initial settlement in the city. They frequently rely on job placement brokers to place them into jobs upon arrival, with positions such as domestic work normally including accommodation. Methods This is a qualitative study undertaken at the two largest bus stages in Addis Ababa, which are points of arrival for a large number of migrants from rural areas. Three categories of respondents were interviewed in-depth: migrant young women who had arrived within the last few days, job placement brokers who are located in and around the bus station, and market women/vendors at the bus stations who interact with both migrants and brokers. Results Migrant girls' point of arrival was an inflection point of risk, especially among girls who were on their own, not accompanied or met at the bus terminal and lacking in plans or preparation of accommodation. Such girls were targeted by thieves at the bus station and by unscrupulous brokers, some of whom forced girls into sexual relations before placing them into paid work. In contrast, market women and some well-meaning brokers took steps to protect girls such as providing temporary accommodation. Conclusion This research underscores the need for intensified support to rural-urban migrants to ensure safety and security at the time of arrival at their destination. This includes promotion of pre-migration education and planning; safety assets including sufficient money, cell phones and alternative contacts in the city; and arrangement for immediate, safe and secure accommodation. As a result of the study, a pilot program has been developed, using local resources to extend support for newly arriving migrant girls and young women.